Tunnelled peritoneal drainage catheter placement for the palliative management of refractory ascites in patients with liver cirrhosis. Issue 2 (28th February 2020) - Corrigan, Margaret; Thomas, Rhodri; McDonagh, Joanne; Speakman, John; Abbas, Nadir; Bardell, Sara; Thompson, Fiona; Holt, Andrew; Jones, Robert; Willis, Andrew; Karkhanis, Salil; Rajoriya, Neil
Abstract : Objective: Refractory ascites is an established indication for liver transplantation. While transplantation is regarded as the definitive therapy for this condition, many patients are unsuitable due to comorbidity or frailty. Alternatives such as transjugular intrahepatic portosystemic shunt (TIPSS) and large-volume paracentesis can lead to complications, including encephalopathy, circulatory and renal dysfunction, and protein–calorie deficiency that may accelerate sarcopenia. Cost and complication rates limit therapies such as alfapump. While there are data to support the use of indwelling catheters in the management of patients with malignant ascites, there is limited evidence to support their routine use in the context of end-stage liver cirrhosis. Here we describe our centres' experience using indwelling tunnelled ascitic drains over a 6-year period. Methods: A retrospective review of data (January 2012–May 2018) was undertaken for all patients with refractory ascites who underwent a tunnelled ascitic drain. Demographics, disease aetiology, procedure data and follow-up data were obtained through interrogation of electronic records and reports. Results: Twenty-five drains were placed. All procedures were technically successful with no immediate complications. Six patients were readmitted following their index admission with abdominal pain and suspected infected ascites (although only two had a positive ascitic fluid culture). There were three cases of abdominal wall cellulitis and three of leakage around the tunnel site; all managed conservatively. Conclusion: Indwelling drains appear an effective strategy for palliative management of select patients with liver cirrhosis complicated by refractory ascites who are not amenable to undergo TIPSS or transplantation. While complications can occur, these are most usually minor and can be managed on an outpatient basis.